A FIRST PRINCIPLES STUDY ON INTERCALATION VOLTAGE AND REDOX MECHANISM FOR MONOCLINIC NA3V2(PO4)3 AS SODIUM ION BATTERY CATHODE MATERIAL - Pradipta Wijaya, Abel
Sodium ion battery (SIB) is a promising alternative as energy storage system (ESS) due to its raw material abundance compared to lithium ion battery (LIB). However, the electrochemical performance of SIB is still not comparable to LIB due to larger ionic radius that hinders in the intercalation process when directly using electrodes that work with LIBs. Na3V2(PO4)3 or better known as NVP, is a promising SIB cathode material with its 3D framework NASICON structure giving it good structural stability and fast sodium ion conduction network. The majority of earlier experimental studies shows that NVP exhibit rhombohedral R3-c symmetry. However, one study conducted by Chotard in 2015 reveals that NVP appears to undergo a monoclinic C2/c distortion below ambient temperatures. The physical and electrochemical properties of this NVP crystal phase is limited. To achieve better understanding of NVP as SIB cathode material, further research needs to be conducted. In the field of battery research, the physical properties of materials is used to study intercalation voltage and the redox mechanism among others. This research is done with a first principles or ab-initio approach based on density functional theory or DFT. A generalized gradients approximation (GGA) based exchange-correlation functional is used to account for electronic contributions in the studied material. In our research, the GGA developed by Perdew-Burke- Ernzerhof (PBE) is used. As battery cathodes are solid state materials, we also opted to use revised PBE for solids (PBEsol) and examine the results between the two exchange-correlation functional. The intercalation voltage of monoclinic NVP shows similar values between the two exchange-correlation functionals, with 1,89 – 2,64 V using PBE and 1,84 – 2,65 V using PBEsol. These values are higher than 1,41 – 2,35 V, which is the voltage of the rhombohedral NVP counterpart done by our fellow research colaborator. The predicted voltage using only PBE and PBEsol is still lower than reported experimental findings of 3,30 – 3,40 V. It is crucial to delve into the electronic structure or redox mechanism of NVP, particularly of vanadium. The redox mechanism of NVP can be studied from vanadium (V) magnetization moment and its bond length with oxygen throughout different concentrations of sodium ion in NaxVP. The results using PBE and PBEsol also